Synthesis and Characterization of Mn+2 , Fe+2 , Co+2 , Ni+2 ,Cu+2 and Cr+3 Complexes With a Bidentate Schiff Base Ligand - Najla H. Taher (College of Education for Pure Sciences, 2008)
ABSTRACT Metal complexes of general formula [M(L)2Cl2] and [Cr(L)2Cl2]Cl {where M is Mn(II), Fe(II), Co(II), Ni(II) and Cu(II) and L (2,3- Bis (N-hexylimino) butane) is a Schiff base formed by condensation of 2,3-butanedione and hexylamine}, have been prepared (in 1:2 metal: ligand molar ratio). The complexes were characterized by analytical, spectral, magnetic and conductance measurements. IR spectra show that the nitrogen of the azomethine groups takes part in coordination. Magnetic measurements and electronic spectral studies suggest an octahedral structure for all complexes. Conductance measurements show a non electrolytic nature of the complexes, with the exception of the [Cr(L)2Cl2]Cl compound with a 1:1 electrolytic nature.